Current trends in articular cartilage research: a bibliometric analysis of the 50 most-cited clinical articles over the last 10 years - McKinley, Matthew T.; Oyedemi, Oluwatosin O.; Childers, Justin T.; Mowers, Colton C.; Jackson, Garrett R.; DeFroda, Steven F.; Nuelle, Clayton W. (International Journal of Research in Orthopaedics, 2026)
Articular cartilage lesions are a frequently encountered pathology during arthroscopic procedures and present a significant challenge. The purpose of this study was to conduct a bibliometric analysis to identify the 50 most cited clinical publications on treatments for cartilage surgery from the past decade, providing an updated overview of influential research and emerging trends in treatment strategies. A literature search was performed in October 2025 using the search terms of “cartilage treatment” OR “cartilage surgery” OR “cartilage repair” were used and filtered to include only those published between 2015 through 2025. The 50 most cited articles were identified and independently reviewed by two authors. Methodological quality was assessed using the Modified Coleman Score, and randomized controlled trials (RCTs) were evaluated using the Revised Tool for Risk of Bias in Randomized Trials (RoB 2.0) tool. A total of 21,640 articles were identified in the initial search. The 50 most cited articles were published between January 2015 and January 2021 and had 6407 total citations (mean±standard deviation, 128.1±63.2) (range, 73-366). Study designs of most cited articles included case series (n=26 studies, 52%), RCTs (n=12 studies, 24%), and cohort (n=12 studies, 24%) designs. The mean modified Coleman was 68.0±8.8 (range, 53-85). The journals publishing the most cited articles were the American Journal of Sports Medicine and Cartilage. High-impact cartilage research has shifted toward MSC-based therapies, surpassing ACI/MACI, while overall methodological quality continues to improve.